Infection with haemoplasma species in 22 cats with anaemia. Issue 2 (February 2016) - Weingart, Christiane; Tasker, Séverine; Kohn, Barbara
Objectives: Information regarding the clinical course of natural infection with feline haemotropic mycoplasmas (haemoplasmas) is limited. The objective of the study was to describe the clinical findings and course of disease in naturally infected cats with haemoplasmosis and anaemia. Methods: A retrospective analysis was performed on patient data from cats presenting with anaemia and haemoplasma infection regarding signalment, clinical signs, laboratory data and course of infection. The diagnosis was confirmed by conventional haemoplasma PCR analysis. Results: Haemoplasma infection was found in 22 anaemic (haematocrit 5–25% [median 17%]; reference interval 30–44%) cats (' Candidatus Mycoplasma haemominutum', n = 12; Mycoplasma haemofelis, n = 3; ' Candidatus Mycoplasma turicensis', n = 2; species not determined, n = 4; coinfection with all three species, n = 1) between 2005 and 2014. Thirteen of the cats had concurrent diseases. All cats underwent antibiotic treatment; 15 cats received blood products. Six cats were euthanased within 11 weeks owing to concurrent disease, persistent severe anaemia or financial constraints. Ten cats underwent follow-up for a period of 14–199 weeks (median 26 weeks). Haemoplasma PCR was negative in 5/7 cases after 3–23 weeks. PCR remained positive in two cases after 18 and 199 weeks, respectively. Reactivation of the haemoplasma infection occurred in two cats, once and three times, respectively, up to 177 weeks after initial presentation. Reactivation was suspected in two further cases. Owing to concurrent disease, four of the 10 follow-up cats were euthanased 14–180 weeks after initial presentation. Conclusion and relevance: Infection with haemoplasma species is often chronic, can reactivate months later and is rarely a reason for euthanasia.